2012
DOI: 10.1074/jbc.m112.394759
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Yeast Sulfhydryl Oxidase Erv1 Reveals Electron Transfer of the Disulfide Relay System in the Mitochondrial Intermembrane Space

Abstract: Background: Mia40 is regenerated by the sulfhydryl oxidase Erv1 in the disulfide relay system. Results: Crystal structures of the Erv1 core domain and full length of Erv1 were determined. Conclusion: The Erv1 N-terminal amphipathic helix is critical for electron transfer from Mia40 to the core redox center of Erv1. Significance: This is the first structural snapshot of the electron transfer process in Mia40-Erv1 disulfide relay system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
2
27
0
3
Order By: Relevance
“…For example, the mutation may affect the interactions between Trp 183 (next to Arg 182 ) and other nearby aromatic residues (e.g. Trp 179 ) or, alternatively, it could affect the interaction between FAD and the aromatic residues that help in stabilizing it [6,9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the mutation may affect the interactions between Trp 183 (next to Arg 182 ) and other nearby aromatic residues (e.g. Trp 179 ) or, alternatively, it could affect the interaction between FAD and the aromatic residues that help in stabilizing it [6,9].…”
Section: Resultsmentioning
confidence: 99%
“…Because this arginine residue is conserved in other ALR homologues (Figure 1b), the authors also used yeast to show that the corresponding erv1 R182H mutant strain displayed genetic instability of the mtDNA, altered mitochondrial morphology, a temperature-sensitive growth phenotype and reduced cyt c oxidase (complex IV) activity [24]. Protein characterizations of human ALR have since then shown that the R194H mutation affects the thermal stability, FAD-binding and proteolysis The X-ray crystal structure of yeast S. cerevisiae Erv1 core domain residues 84-188 (c) and a zoomed in of the structure showing the hydrogen bond formed between Arg 182 and the 2 OH of the ribose moiety of FAD (d) (PDB code: 4EOH [9]). The structures were generated using the PyMOL software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The erv1-2 and erv1-5 strains each contain single point mutations in the ERV1 gene creating N166D and C159S substitutions, respectively (37). Asn-166 and Cys-159 are both located near the FAD binding site, with Cys-159 forming a structural disulfide with Cys-176 (36). As such, the C159S Erv1 mutant exhibits decreased FAD binding in vitro (38), whereas both erv1-2 and erv1-5 are impaired in import of IMS proteins (3,37,39).…”
Section: Resultsmentioning
confidence: 99%
“…Such inter-subunit redox communication was also proposed for lfALR [24]. The structural aspects of the communication between Mia40 and Erv1p or ALR have received considerable attention [22, 2426]. …”
Section: Introductionmentioning
confidence: 99%